Leadership in higher education: Private higher education. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2008)
In recent years, dramatic changes in higher education (HE) have occurred on a global scale and leaders in education are faced with new challenges and opportunities. Higher education can no longer be viewed solely as a national endeavour as overseas universities actively position themselves as alternate providers of HE. Local HE institutions (HEIs) are also looking outward, actively attracting international students to enrol in local institutions, or going global by setting up overseas branches. Recognising these changes, the Ministry of Higher Education has drawn up the National Higher Education Strategic Plan in 2007 to reform HE in the country. Within this Plan, leadership features prominently and in fact forms one of the five pillars for transforming HE in Malaysia.